2019
DOI: 10.1001/jamafacial.2019.0243
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking and Other Factors With the Outcome of Mohs Reconstruction Using Flaps or Grafts

Abstract: IMPORTANCE Smoking, a common lifestyle trait, is considered by many surgeons to be a major risk factor for postoperative complications. However, in the literature on local reconstruction, the association between smoking and the rate of postoperative complications after cutaneous tissue transfer is not well characterized. OBJECTIVETo study the outcomes of flaps and grafts used in Mohs micrographic surgery reconstruction with respect to smoking status and patient-specific and surgery-specific variables.DESIGN, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
2
15
1
3
Order By: Relevance
“…In 2019, Wang et al studied the outcomes of flaps and grafts in Mohs reconstruction with respect to smoking and revealed that both active smoking and former smokers were at increased risk for complications. 28 In our analysis, we did not make a distinction between active and former smokers. Stemming from the aforementioned findings, this separation may help future research in determining if such a correlation exists.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Wang et al studied the outcomes of flaps and grafts in Mohs reconstruction with respect to smoking and revealed that both active smoking and former smokers were at increased risk for complications. 28 In our analysis, we did not make a distinction between active and former smokers. Stemming from the aforementioned findings, this separation may help future research in determining if such a correlation exists.…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis is more commonly encountered following flap reconstruction given that vascularity of the flap is limited to the pedicle 48 . The literature suggests that higher rates of complications occur with flap and graft repairs; large flaps, interpolation flaps, or flap‐graft combinations are more commonly associated with necrosis and other complications 15,49,50 . Causes of complete or partial graft necrosis include hematoma, graft‐bed contact disruption, infection, smoking, and excessive electrocoagulation of the wound base 51 …”
Section: Necrosismentioning
confidence: 99%
“…In a retrospective analysis of 916 flaps and full‐thickness grafts, heavy smokers (>1 pack/d) developed necrosis three times more frequently than never smokers, low‐level smokers (<1 pack/d), or former smokers 52 . A more recent study also demonstrated that current and former smokers undergoing graft and flap repair following MMS are more likely to experience acute postoperative complications including necrosis 50 . Encouraging patients to stop smoking before surgery and in the postoperative period will likely reduce the risk of acute complications and allow for enhanced wound healing.…”
Section: Necrosismentioning
confidence: 99%
See 1 more Smart Citation
“…3 There are various risk factors that predispose patients to complications that should be screened for and managed to the best extent possible in every patient, including smoking, immunosuppression, hypertension, diabetes, blood dyscrasias, inflammatory skin disorders, prior radiation therapy, and history of hypertrophic and/or keloid scarring. [4][5][6][7] Here, we assume that the surgeon is aware of and has taken prophylactic measures to mitigate such risk factors preoperatively. The purpose of this narrative review is to provide a range of postoperative management options, and review the evidence for each modality, so that reconstructive surgeons can stay up to date on current literature, as well as understand gaps in the literature for future research.…”
mentioning
confidence: 99%